Burden of mental distress in the US associated with trust in media for COVID-19 information. (21st November 2022) - Jalan, Madhu; Riehm, Kira; Agarwal, Smisha; Gibson, Dustin; Labrique, Alain; Thrul, Johannes
Summary: During the COVID-19 pandemic, news and social media outlets have played a major role in dissemination of information. This analysis aimed to study the association between trust in social and traditional media and experiences of mental distress among a representative sample of US adults. Data for this study came from National Pandemic Pulse, a cross-sectional, nationally representative survey that sampled participants on the Dynata platform. Participants included 6435 adults surveyed between 15–23 December 2020. Ordinal logistic regression analyses examined the associations of trust in (i) social media, (ii) print media, (iii) broadcast TV and (iv) cable TV, for COVID-19-related information with self-reported mental distress (4-item Patient Health Questionnaire), controlling for sociodemographics and census region. Compared with those who distrusted social media, those who trusted social media had 2.09 times (95% CI = 1.84–2.37) greater adjusted odds of being in a more severe category of mental distress. In contrast, compared with those who distrusted print media, those who trusted print media had 0.80 times (95% CI = 0.69–0.93) lower adjusted odds of being in a more severe category of mental distress. No significant associations were found between mental distress and trust in broadcast or cable TV for accessing news about COVID-19. Trust in different news outlets may be associated with mental distress during public health emergencies like the COVID-19 pandemic. Future studies should explore mechanisms behind these associations, including adherence to best practices for crisis reporting among different media sources and exposure of individuals to misinformation. Lay Summary: During the COVID-19 pandemic, both, traditional channels like print, TV and cable news, as well as social media, have been major sources to obtain news about the pandemic. In this manuscript, we study the association between trust in social and traditional media and symptoms of mental distress among a nationally representative sample of 6435 US adults surveyed in December 2020. Our findings show that those who reported trusting traditional print media were less likely to report more severe mental distress. Conversely, those who reported trusting social media were more likely to report more severe levels of mental distress. This highlights the urgent need for understanding the diffusion patterns of misinformation and rumors that circulate on social media, and consumers' reactions to them. It is important that during a public health emergency, we follow best practices for crisis communication to reduce panic, address uncertainty, promote protective behaviors and mental health.